Impact of Green Transformational Leadership on Corporate Environmental Performance with the Mediating Role of Dynamic Capabilities - Muhammad Yaseen Nawaz; Ahmed Jamil; Alia Akram; Kanza Saleem (Indus Journal of Social Sciences, 2025)
This research examines the impact of Green Transformational Leadership (GTL) on Corporate Environmental Performance (CEP) with the mediating role of Dynamic Capabilities (DC). Modern environmental consciousness and sustainable practices force businesses to develop eco-friendly approaches aligned with ecological sustainability. This research evaluates the influence GTL has on CEP while maintaining that Dynamic Capabilities serve as an essential mediator between these variables. The research bases its findings on the Resource-Based View and the Dynamic Capabilities Theory to study how leadership behaviour focused on environmental consciousness activates organisational transformation and innovation for better eco-friendly results. GTL is an ecological leadership framework that inspires staff members to adopt green practices, create joint environmental visions, and stimulate sustainable development. The ability of a firm to adapt its internal and external competencies through integration, building, and reconfiguration functions is an essential mechanism which GTL uses to impact CEP. In this study, the convenience sampling technique is used. The population selected for this study is the Manufacturing SMES employees in the Pakistan district. Employees are the ones who are directly linked to the customers. As the population is very large and unknown, the sample size would be 300 using sample size estimation. The unit of analysis is the employees working in automobile companies in South Punjab. Descriptive statistics, correlation analysis, reliability and validity were used in the data analysis, which was done using SPSS and AMOS. GTL leads to substantial CEP improvement in organisations through their dynamic capabilities, which function as partial mediators according to predicted findings. This research helps expand the knowledge on sustainable leadership and environmental management through a quantitative assessment of how leadership impacts ecological performance by developing internal abilities. Organizations and policymakers can use these findings to develop strategies to use transformational leadership for sustainable innovation and environmental responsibility.